The Meaning of Traditional Expressions in Muritana Marriages in Central Sumba District, East Nusa Tenggara - Wali, Eva Arnas; Setyowati, Endang; Rachman, Anita Kurnia (Journey: Journal of English Language and Pedagogy, 2026)
Language is an important element of cultural identity that must be preserved because it is passed down from generation to generation. In the Muritana community of Central Sumba, traditional expressions are still maintained, especially in traditional marriage ceremonies. This study aims to identify, describe, and analyze the meanings of traditional expressions used in the marriage rituals of the Muritana ethnic group in Central Sumba Regency, East Nusa Tenggara. The study employs an ethnolinguistic approach using the theoretical framework of James W. Underhill to understand how language reflects the worldview, cultural values, and social structure of the community. This research uses a qualitative method with data in the form of words, phrases, and sentences spoken in traditional marriage rituals. The data were obtained through observation, interviews with traditional elders and community leaders, and documentation. The results show that traditional expressions in Muritana marriage rituals contain symbolic meanings that reflect respect, the strengthening of kinship ties, and the maintenance of social harmony between families. For example, the expression “Ndima mai ngia ti umma nanni anamu” conveys humility and respect from the groom’s family when proposing to the bride’s family. These expressions also indicate the patrilineal social structure and the moral values upheld by the Muritana community. Therefore, traditional language in marriage ceremonies not only functions as a means of communication but also as a cultural medium that preserves identity, social order, and the continuity of Muritana traditions.